Dead before they wake [videorecording (DVD)] - Shepka, Nathan; Shepka, Nathan; Cordell, Grace; Sumal, Manjot; Nasif, Kareem (Deskpop Entertainment, 2025)
Alex, a nightclub bouncer, is hired by a retired lawyer to find a missing teenage girl. His search uncovers a sex trafficking ring operating in the seedy underbelly of the city. Can Alex find personal redemption in the girl's safe return?